Transverse colon stenosis following laparoscopic total gastrectomy for gastric remnant carcinoma - Cicek, Egemen (J Minim Access Surg, 2019)
Laparoscopic surgery for remnant gastric cancer has been reported in a limited number of cases, and data on post-operative complications are lacking. A 58-year-old male was admitted with remnant gastric cancer. He had undergone open subtotal gastrectomy 9 years ago for gastric cancer. Laparoscopic total gastrectomy was performed, and he was discharged on the 10(th) day uneventfully. The patient had complained of nausea and vomiting in the 2(nd) post-operative month. He clinically and radiologically diagnosed as ileus and required open emergency surgery. There was a transverse colon stenosis near the splenic flexure. Hartmann's procedure was done, and he was discharged on day 17. We have limited knowledge about colonic complications after laparoscopic gastric surgery. The development of stenosis in the transverse colon is one of these complications that should be kept in mind. As far as we know, such a complication has never been reported before.